2010
DOI: 10.1158/0008-5472.can-09-3826
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Suppressive Functions of Leucine Zipper Transcription Factor–Like 1

Abstract: Human leucine zipper transcription factor-like 1 (LZTFL1) is a novel gene with unknown biological functions. It is located in the chromosome region 3p21.3, a hotspot for tumor suppressor genes. To understand the biological functions of LZTFL1, we surveyed the expression level of LZTFL1 in tumor and normal samples in tissue microarrays and a clinical archive of 84 gastric cancer specimens using immunohistochemistry. We found that LZTFL1 is expressed highly in the epithelial cells of normal tissues and is signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 17 publications
(17 reference statements)
2
54
0
Order By: Relevance
“…Wang et al have suggested that cytoplasmic LZTFL1 and E-cadherin inhibit β-catenin nuclear transport and EMT processes in GC cells, thereby inhibiting their invasion and metastasis [7]. This is in agreement with the results obtained in the present study, in which LZTFL1 protein expression was positively correlated with E-cadherin, and negatively correlated with β-catenin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Wang et al have suggested that cytoplasmic LZTFL1 and E-cadherin inhibit β-catenin nuclear transport and EMT processes in GC cells, thereby inhibiting their invasion and metastasis [7]. This is in agreement with the results obtained in the present study, in which LZTFL1 protein expression was positively correlated with E-cadherin, and negatively correlated with β-catenin.…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained in this study showed that LZTFL1 in epithelial cells of normal tissues was highly expressed, but was lowly expressed in samples of corresponding invasive cancer group [7]. LZTFL1 expression is of prognostic significance in GC.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The percentage of ASCpositive cells in carcinoma (epithelial) cells was calculated in the printed image (300 dot per inch). We classified the sections into three grades (ASC score 1; positive cells 33%, score 2; 34%-66%, and score 3; 67%-100%) according to the modified method of Wei et al 20 Each section was examined by two independent examiners (H. Ko and H. Ai) and there was no disagreement in the final ASC score.…”
Section: Studies In Clinical Samplesmentioning
confidence: 99%
“…Although we expected to see well-known genes for cell death in Group II, we could not find such genes except for NDRG1 (Stein et al, 2004). However, we were able to identify LZTFL1, a known transcription factor and tumor suppressor gene related to growth arrest (Wei et al, 2010), as a novel ER stress responsive gene from this group. Contrary to the expectation, several genes from the group are known to function in UPR and ERAD (marked with *).…”
Section: Candidates Of Er Stress Responsive Genesmentioning
confidence: 95%